Effects of Persistent Organic Pollutants on Reproductive Hormones in Male Polar Bears (Ursus Maritimus) from Svalbard - Hansen, Ingunn Tjelta (Institutt for biologi, 2012)
PCBs and other environmental contaminants have been found to have an effect on steroid hormones in polar bears (Ursus maritimus). The purpose of this study was to investigate the effect of persistent organic pollutants (POPs) on the steroidogenesis in male polar bears from Svalbard. Blood samples from male polar bears (n=23) were collected at Svalbard, Norway in April 2008 as a part of the International Polar Year-project, BearHealth. The sampled individuals were between 3-21 years, where individuals under 5 years (n=6) were categorized as subadults. Serum and plasma samples were analysed for steroid hormones (pregnenolone (Pre), progesterone (Pro), androstenedione (AN), dehydroepiandrosterone (DEA), testosterone (TS), dihydrotestosterone (DHT), estrone (E1), estradiol-17α (E2-α) and estradiol-17β (E2-β)) with a recently developed gas chromatography-tandem mass spectrometry (GC-MS/MS) determination method, whereas cholesterol concentrations were measured by Reflotron. The environmental contaminants (HCB, α‐HCH, β‐HCH, oxychlordane, trans‐nonachlor, mirex, p,p'-DDE, p,p'‐DDT, PCB‐47, PCB‐74, PCB‐99, PCB‐101, PCB‐128, PCB‐137, PCB-138, PCB‐153, PCB‐170, PCB‐180, PCB‐183, PCB‐187, PCB‐194, PCB‐206, PCB-105, PCB-114, PCB-118, PCB-156, PCB-157, PCB-167, PCB-189, 4'-OH-CB107, 4'-OH-CB130, 3'-OH - CB138, 4‐OH‐CB146, 4'-OH‐CB159, 4'-OH-CB172, 3'-OH-CB180, 4-OH‐CB187, BDE-47, BDE-154) included in this study were analysed by gas chromatography-electron capture detection (GC-ECD) or GC/MS. Multivariate regression analysis, principal component analysis (PCA) and orthogonal partial least squares (OPLS) regression, were performed to investigate the influence of the contaminants on the steroid hormones in the adult individuals. Only the OPLS model with DHT as the response variable was significant. Most of the environmental contaminants had a significantly negative contribution on the variation in dihydrotestosterone concentrations. Based on the statistical analyses, the poly-ortho PCBs and HCB might be more central in ...